REVIEW OF VEHICLE TELEMATICS USAGE BASED INSURANCE - CONTRIBUTION TO SUSTAINABLE INSURANCE STRATEGY - Nedić, Aleksandar; Nedić, Nemanja; Stevanović, Igor; Stanojević, Darko (Journal of Applied Engineering Science, 2014)
The purpose of insurance is to provide security for the clients and its partners, by perfectly and responsibly understand, manage, monitor and carry the risk. As a powerful motor of global industry, insurance also have a potential to contribute enhancement of society, economy and governance, with strong positive influence on the environment. Sustainable insurance is a strong commitment of the insurance sector to recognize the sustainable values and determination to integrate these values in their strategy. In the new way of looking to the future, principals of insurance sector are in the best position to initiate and to assist in resolving complex global challenges-climate change issues and impoverishment of natural resources. In this paper will be discussed about the auto Telematics Usage Based Insurance products. These products are promoted by the insurance sector in accordance with natural progress of society and legal framework, evolution of technology and changes in demands. They can be classified as perspective solutions for sustainable insurance, because they directly affect environmental, safety, energy and resources saving, and overall social improvement issues.